ATIM-02. TUMOR TREATING FIELDS IN COMBINATION WITH BEVACIZUMAB IN RECURRENT OR PROGRESSIVE MENINGIOMA IN A PHASE 2 STUDY. (5th November 2018) - Kumthekar, Priya; Kruser, Tim; Sachev, Sean; Raizer, Jeffrey; Grimm, Sean; Dixit, Karen
Abstract: For patients with WHO grade II meningioma, the two-year and five-year overall survival is 93% and 73%, respectively. Patients with malignant meningioma (grade III) have significantly worse outcomes, with five-year overall survival rates of 42%. The recurrence rate remains high with overall survival is as low as 3 years after diagnosis. The current treatment for high grade and recurrent meningioma includes maximal safe surgical resection and radiation. Tumor Treating Fields (TTFields) and Bevacizumab (BEV) have been reported to potentially show activity in recurrent and high-grade meningioma. The combination of TTFields and BEV may provide a viable treatment option for patients with recurrent and high grade meningioma. This Phase 2 Simon two-staged, non-randomized, open-label phase II, single arm clinical trial [NCT02847559] will investigate the combination of TTFields and BEV in recurrent or progressive meningioma. The primary endpoint is progression free survival (PFS) at 6 months (PFS-6). Secondary endpoints include overall survival (OS); Tumor Response Rate (TRR), Objective Response Rate (ORR); and Quality of Life (QOL) using FACT-Br questionnaire. Patients (N=27), including those who have failed prior BEV therapy, will receive BEV IV 10 mg/kg over 30–90 minutes on days 1 and 15 of courses 1–4. Beginning on day 1 of course 5, patients may choose to receive bevacizumab IV 15 mg/kg every 3 weeks or remain on the every 2-week schedule. Patients will receive TTFields 200 KHz (1–3 V/cm) daily for at least 18 hours/day. This study is powered to detect a true PFS-6 rate of 20% with 80% probability (80% power) and a true PFS-6 rate of 5% with 90% probability (alpha=0.10). 27 patients were planned to have 24 evaluable patients. To-date 4 patients have been enrolled at the principal site and at least two additional sites are planned to open this year.